Matching digital companions with customers: The role of perceived similarity - Katja Gelbrich; Alina Kerath; HaeEun Helen Chun (Psychology & Marketing, 2023)
Digital companions are an advanced form of digital agents that do not only provide advice and support but accompany people on their day-to-day customer journeys. This article sheds light on the psychological processes underlying customers' responses to these digital companions (i.e., virtual friends or co-consumers). We propose that framing them as matched with customers on goal-relevant attributes (i.e., attributes related to customers' consumption goals) fosters positive customer outcomes (i.e., consumption enjoyment and positive word-of-mouth), mediated by perceived similarity in these attributes. Importantly, in this matching context, humanlikeness serves as a boundary condition for perceived similarity to occur. Furthermore, the effect of perceived similarity on customer outcomes is driven by perceived connectedness. In Study 1, in the context of experiential learning, we identified shared interest and personality as goal-relevant attributes underlying perceived similarity. With the manipulation of the match frame and humanlike versus artificial voice of the digital companion, Study 2 supports our propositions and highlights shared interest, but not personality, as the core driver. We provide recommendations on how to design and market digital companions to foster connection and favorable customer outcomes.
Keywords: 650; co-consumers; consumption enjoyment; digital agents; digital companions; human-likeness; perceived connectedness; perceived goal-relevant similarity; virtual friends